Multiple Cis-acting Polypyrimidine Tract Elements Regulate a Cooperative Mechanism for Triticum Mosaic Virus Internal Ribosomal Entry Site Activity - Jaramillo-Mesa, Helena; Fischer, Emma; Rakotondrafara, Aurélie M. (Frontiers in Plant Science, 2022)
Diverse elements within the 5’ untranslated region of an mRNA can influence the translation efficiency at the main AUG codon. We previously identified a core picornaviral like Y16X11-AUG motif with 16-nt polypyrimidine CU-tract separated by an 11-nt spacer sequence from the 13th AUG codon, which is recognized as the preferred initiation site within the Triticum mosaic virus (TriMV) internal ribosome entry site (IRES) element. The motif is proposed to function as an internal ribosomal landing site at the designated start codon. Here we exposed the cooperative role of multiple CU-rich segments flanking the TriMV YX-AUG motif to reach and drive internal initiation of translation at the preferred start site. We propose that these auxiliary domains may enhance the ribosome capacity and their delivery at proximity of the correct initiation site. These polypyrimidine tracts can be modulated with a cryptic AUG in a position-dependent manner to replace the native YX-AUG motif, and thus uncovering a new layer of control of start codon selection. In line with these observations, mass spec analysis of proteins directly interacting with translationally impaired TriMV IRES mutants that bear these motifs indicated an enrichment in 40S and 60S ribosomal related proteins, revealing a new function of polypyrimidine tracts to regulate IRES-driven translation. Accessibility of these RNA regions for in trans interaction was validated by SHAPE analysis of the entire TriMV leader sequence and supported by the ability of anti-sense oligonucleotides designed to block the CU-tracts accessibility to impair IRES activity. This is the first evidence that defines the core modular domains required for ribosomal recruitment and start codon selection in a complex, multi-AUG viral 5’UTR for translation in plants.